2018
DOI: 10.18203/2394-6040.ijcmph20185078
|View full text |Cite
|
Sign up to set email alerts
|

The educational issues of male nursing workforce from the perspective of male nursing students: a qualitative study from Turkey

Abstract: Background: The aim of the study was to determine the effects of gender on vocational training of male students who were enrolled in two university undergraduate nursing programs in Turkey.Methods: This qualitative study was carried out in 2014-2015. This qualitative study was carried out in University located in the northwest of Turkey and in University located in the west of Turkey in 2014-2015. The students were third and fourth year-students. In-depth interviews were conducted with students by using an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The results showed that male nursing students do not gain sufficient knowledge and skills about services, including care before and after delivery and family planning, which are categorized as primary health services. They are also not given the opportunity to put their knowledge into practice [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that male nursing students do not gain sufficient knowledge and skills about services, including care before and after delivery and family planning, which are categorized as primary health services. They are also not given the opportunity to put their knowledge into practice [ 10 ].…”
Section: Introductionmentioning
confidence: 99%